Vehicle electrical system safety detection method - QU XIAOLEI; LIU WANFA (2017)
To overcome the problem that after replacement of a battery of an electric vehicle, due to lack of standardization of battery installation and lack of battery management system parameter regulation, and running-in of a new battery itself and the power supply condition after replacement of the battery, inaccurate electric quantity detection is caused and safe operation of the vehicle is influenced, the invention provides a vehicle electrical system safety detection method, thus the battery management system of the electric vehicle can actively and intelligently learn characteristic parameters of the new battery, and obtain a regulation coefficient, and the circumstance is prevented that inaccurate setting of a threshold value of the battery management system or a battery management chip of the vehicle itself affects electric vehicle starting and normal operation of systems or units such as sound equipment and air conditioning and even affects normal running of the vehicle. 为了克服电动车辆在更换电池后由于电池安装不规范和缺乏对电池管理系统参数调教